Personal Resources in AI-Assisted Translation - Pietrzak, Paulina (Research in Language, 2025)
Translation has been fundamentally reshaped by artificial intelligence (AI) technology, which increasingly dictates workflows that boost human efficiency but diminish human agency. While these tools may indeed enhance efficiency, they simultaneously erode the cognitive and reflective dimensions of translator practice and education. This article highlights personal resources as essential for sustaining judgment and professional autonomy. AI-assisted tools have indeed transformed the ways translators work and learn, but they cannot replace the uniquely human capacity for purposeful self-development, which is the central focus of this article. The article emphasises how fostering personal resources in translator education can empower future professionals to not only adapt to technological change but to shape it consciously and ethically. The underlying assumption is idealistic, perhaps, yet essential for preserving translation quality and the evolving identity of translators. Translator education should nurture individuals who are not only competent but also human, humane and fully engaged in their professional and personal growth.